The Influence of Board Diversity and Family Ownership on the Financial Sustainability of IDX-Listed Companies - Santi Yopie; Sheila Septiany; Kerlyn Yoan Sondakh (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of gender diversity on the board of directors and the presence of foreign directors on the financial sustainability of companies. It also investigates the moderating role of family ownership in the relationship between board diversity and financial sustainability, focusing on companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A quantitative approach with a causal-comparative design was employed. The study used secondary data obtained from corporate annual reports. Data were analyzed using multiple linear regression and moderation tests. The results indicate that board size has a significant positive effect on financial sustainability, while the presence of foreign directors shows a marginally significant negative effect. The leverage and firm age variables have marginally significant positive effects on financial sustainability, whereas gender diversity, board independence, and firm size do not show significant effects. The regression model is significant at the 5% confidence level, with the independent variables explaining 54.67% of the variation in financial sustainability.